2020
DOI: 10.1186/s12885-020-06742-3
|View full text |Cite
|
Sign up to set email alerts
|

Change in public awareness of colorectal cancer symptoms following the Be Cancer Alert Campaign in the multi-ethnic population of Malaysia

Abstract: Background: Colorectal cancer (CRC) cases are detected late in Malaysia similar to most Asian countries. The Be Cancer Alert Campaign (BCAC) was a culturally adapted mass media campaign designed to improve CRC awareness and reduce late detection in Malaysia. The evaluation of the BCAC-CRC aimed to assess campaign reach, campaign impact and health service use. Methods: Participants aged ≥40 years (n = 730) from randomly selected households in Selangor State Malaysia, completed interview-based assessments. Campa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
4
22
0
Order By: Relevance
“…Our study also showed that the greater the level of attention to COVID-19, the greater the negative emotions, which is in agreement with previous research 30 . As a result of strict prevention and control measures, the general awareness and vigilance of residents have increased 31,32 . Since respondents were those who had mobile phones with access to WeChat and decide to participate in the survey, which means that most people get information about COVID-19 mainly through the mass media.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that the greater the level of attention to COVID-19, the greater the negative emotions, which is in agreement with previous research 30 . As a result of strict prevention and control measures, the general awareness and vigilance of residents have increased 31,32 . Since respondents were those who had mobile phones with access to WeChat and decide to participate in the survey, which means that most people get information about COVID-19 mainly through the mass media.…”
Section: Discussionmentioning
confidence: 99%
“…Although the BCAC-BC had greater reach compared with the BCAC-CRC, the BCAC-CRC appeared to be more successful in terms of improving symptoms awareness 25 , perhaps, because of the higher precampaign symptom knowledge/awareness (prompted and unprompted) among the BCAC-BC sample compared with BCAC-CRC participants. Awareness improved significantly at follow-up for three prompted BC symptoms, whereas awareness about all prompted CRC symptoms was improved.…”
Section: Discussionmentioning
confidence: 90%
“…The differential reach that was experienced by ethnic groups was similar to the findings from the BCAC for colorectal cancer (BCAC-CRC) in Malaysia. 25 Different attitudes and behaviours across ethnic groups regarding help seeking may help to explain the apparent discrepancy. For example, US health survey participants who did not seek health information in the media and preferred to trust their health service provider tended to be older and have a lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Recently published findings indicate improvements in symptom awareness at follow-up across ethnic and social strata although, in common with the English experience, evidence of improvements in downstream outcomes was less clear. 28 …”
Section: Introductionmentioning
confidence: 99%